Macroscopic and electric properties in the CdTe-AgI-As2Se3 system. (November 2018) - Kassem, M.; Kassem, H.; Bychkov, E.
Graphical abstract: Highlights: Macroscopic properties of the pseudo-ternary CdTe-AgI-As2 Se3 chalcogenide glasses. Non-monotonic glass transition behaviour with increasing CdTe content. Conductivity measurements of the pseudo-ternary CdTe-AgI-As2 Se3 chalcogenide glasses. Decrease of the Ag + ion transport in the CdTe-AgI-As2 Se3 glasses. Blockage of silver-related preferential conduction pathways by Cd 2+ . Abstract: Chalcohalide glasses in the CdTe-AgI-As2 Se3 system were synthesised and characterised for the first time. Measurements including density, X-ray diffraction (XRD), and differential scanning calorimetry (DSC) were performed. The glass-forming range for (CdTe) x (AgI)0.5- x /2 (As2 Se3 )0.5- x /2 compositions was found to be limited to x ≤ 0.25. The characteristic glass transition T g, crystallisation T x, and melting T m temperatures of the synthesised glasses are reported and the criteria, ΔT = T x -T g, was calculated to evaluate the glass forming ability. Total electric conductivity measurements have shown that the room temperature conductivity decreases drastically with increasing x accompanied by a simultaneous increase of the activation energy. The decrease in the Ag + ion transport cannot be explained by reduction in the total silver concentration alone and a possible structural origin of conductivity changes was proposed and discussed.